2017
DOI: 10.1093/schbul/sbx015
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length and CCL11 Levels are Associated With Gray Matter Volume and Episodic Memory Performance in Schizophrenia: Evidence of Pathological Accelerated Aging

Abstract: Schizophrenia (SZ) is associated with increased somatic morbidity and mortality, in addition to cognitive impairments similar to those seen in normal aging, which may suggest that pathological accelerated aging occurs in SZ. Therefore, we aim to evaluate the relationships of age, telomere length (TL), and CCL11 (aging and inflammatory biomarkers, respectively), gray matter (GM) volume and episodic memory performance in individuals with SZ compared to healthy controls (HC). One hundred twelve participants (48 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 65 publications
3
25
0
Order By: Relevance
“…8,10 Illnesses associated with premature or accelerated ageing, and found with greater prevalence in marginalised people, include schizophrenia, traumatic brain injury, alcohol dependence and HIV infection. [13][14][15][16] Independent of age-related illnesses, cognitive dysfunction may be a critical marker of diminishing robustness in biological systems associated with premature mortality. 17,18 Identifying vulnerabilities for poor long-term outcomes in homeless people is essential to establish priorities for early interventions.…”
mentioning
confidence: 99%
“…8,10 Illnesses associated with premature or accelerated ageing, and found with greater prevalence in marginalised people, include schizophrenia, traumatic brain injury, alcohol dependence and HIV infection. [13][14][15][16] Independent of age-related illnesses, cognitive dysfunction may be a critical marker of diminishing robustness in biological systems associated with premature mortality. 17,18 Identifying vulnerabilities for poor long-term outcomes in homeless people is essential to establish priorities for early interventions.…”
mentioning
confidence: 99%
“…Thus, decreased LTL and increased levels of C-C Motif Chemokine Ligand 11 (CCL11), which crosses the blood-brain barrier and is involved in neuroinflammation, are related with reduced grey matter volume and a longer duration of illness, consistent with the hypothesis that schizophrenia is associated with a pathological accelerated ageing, leading to impaired outcomes in these patients [ 146 ]. Telomere shortening also has a detrimental effect on brain size in healthy individuals, but the association between these parameters is significant only for those older than 50 years [ 147 ], while in schizophrenia patients this relationship was observed at 36 years [ 146 ].…”
Section: Schizophrenia Inflammation and Early Senescencementioning
confidence: 60%
“…Thus, decreased LTL and increased levels of C-C Motif Chemokine Ligand 11 (CCL11), which crosses the blood-brain barrier and is involved in neuroinflammation, are related with reduced grey matter volume and a longer duration of illness, consistent with the hypothesis that schizophrenia is associated with a pathological accelerated ageing, leading to impaired outcomes in these patients [ 146 ]. Telomere shortening also has a detrimental effect on brain size in healthy individuals, but the association between these parameters is significant only for those older than 50 years [ 147 ], while in schizophrenia patients this relationship was observed at 36 years [ 146 ]. In agreement with these results, another recent study has shown that the diagnosis of schizophrenia, more than other possible confounding parameters such as gender, age, cigarette smoking or alcohol drinking, is the most important condition responsible for LTL shortening in these patients, and that major differences in LTL shortening were mainly observed in patients younger than 50 years, while no significant differences were observed in the group of older subjects [ 148 ].…”
Section: Schizophrenia Inflammation and Early Senescencementioning
confidence: 60%
See 1 more Smart Citation
“…Extant literature further demonstrates how shorter LTL may be associated with mortality and several age-related diseases like cancer, cardiovascular disease, type II diabetes, and neurodegenerative disorders such as Parkinson's Disease, Huntington's Disease, and Alzheimer's Disease (AD) (Cai et al, 2013;Degerman et al, 2014;Forero et al, 2016;Herrmann et al, 2018;Honig et al, 2012;Insel, Merkle, Hsiao, & Vidrine, 2012;Ma et al, 2013;Scarabino, Broggio, Gambina, & Corbo, 2017;Wikgren et al, 2014). Some studies have also found relationships between LTL with neuropsychiatric disorders such as depression, anxietyrelated disorders, schizophrenia, and other psychotic disorders, as well as bipolar disorder (Richard, Reitz, Honig, Schupf, & Tamg, 2013;Chang et al, 2018;Czepielewski et al, 2018;Nieratschker et al, 2013, Powell, Dima, Frangou, & Breen, 2018Vasconcelos-Moreno et al, 2017;Wang et al, 2017;Colpo, Leffa, Quevedo, & Carvalho, 2015;Lindqvist et al, 2015). Such aging-, metabolic-, psychiatric-, and inflammation-related conditions have all been associated with cognitive outcomes (Cohen-Manheim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%